2018
DOI: 10.1002/2018gl077525
|View full text |Cite
|
Sign up to set email alerts
|

Thermospheric Expansion Associated With Dust Increase in the Lower Atmosphere on Mars Observed by MAVEN/NGIMS

Abstract: We present for the first time the dramatic variations in atmospheric composition and density at high altitudes from 170 to 220 km in Mars' neutral thermosphere in response to dust increases in the lower atmosphere, observed by the in situ Neutral Gas Ion Mass Spectrometer onboard the Mars Atmosphere and Volatile EvolutioN satellite. The observations reveal that CO2, Ar, N2, CO, and O densities all increase up to ~200% compared to the longer‐term running median densities. The density increases are seen througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 39 publications
0
60
0
Order By: Relevance
“…Although they did not report any temperature observations, Withers and Pratt (2013) had inferred possible cooling in the upper atmosphere based on the apparent decrease in the density enhancement factor between 130 and 160 km using the MGS accelerometer data. A very recent study by Liu et al (2018) has shown possible increase in thermospheric temperature related to local dust storms in MY 32 and MY 33. Elrod et al (2019) have shown NGIMS densities and derived temperatures throughout the time evolution of the PEDE-2018 storm and reported slightly higher scale heights during the onset of the PEDE-2018, but no dayside temperatures were reported during the peak dust storm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they did not report any temperature observations, Withers and Pratt (2013) had inferred possible cooling in the upper atmosphere based on the apparent decrease in the density enhancement factor between 130 and 160 km using the MGS accelerometer data. A very recent study by Liu et al (2018) has shown possible increase in thermospheric temperature related to local dust storms in MY 32 and MY 33. Elrod et al (2019) have shown NGIMS densities and derived temperatures throughout the time evolution of the PEDE-2018 storm and reported slightly higher scale heights during the onset of the PEDE-2018, but no dayside temperatures were reported during the peak dust storm.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements by Mariner 9, Mars Global Surveyor, and SPICAM have shown the responses due to dust storms by the thermospheric structure, especially the neutral and ionospheric densities (Bougher et al, 1999;Cox et al, 2010;Forget et al, 2009;Keating et al, 1998;Stewart & Hanson, 1978;Withers & Pratt, 2013). The upper atmospheric expansion due to the dust storm was also observed in elevated airglow peak heights measured by the MAVEN Imaging Ultraviolet Spectrograph (IUVS) (Gérard et al, 2019) and increased in neutral densities measured by the MAVEN Neutral Gas and Ion Mass Spectrometer (NGIMS) (Elrod et al, 2019;Liu et al, 2018). Forget et al (2009) reported temperatures from altitudes around 130 km using the SPICAM stellar occultation data but did not report any significant effect of dust storms on the temperatures with exception of a few observations.…”
Section: Introductionmentioning
confidence: 94%
“…In fact, according to recent observations, the increase of neutral density in Martian upper atmosphere can significantly increase the photoelectron flux across all energy ranges (Xu et al, ); therefore, the lift of the upper ionosphere may also be related to the variations of neutral density, especially the variations of CO 2 density, which is the main source of the electrons in this region (Wang & Nielsen, ). The latest observations of MAVEN have strongly demonstrated the obvious increase of CO 2 density between 170 and 220 km during dust storms (Liu et al, ). Furthermore, Liu et al () even found that the thermosphere (170–220 km) moved upward by about 10 km during a regional storm, which also suggests that the lift of upper ionosphere may be influenced by the lift of neutral atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…The latest observations of MAVEN have strongly demonstrated the obvious increase of CO 2 density between 170 and 220 km during dust storms (Liu et al, ). Furthermore, Liu et al () even found that the thermosphere (170–220 km) moved upward by about 10 km during a regional storm, which also suggests that the lift of upper ionosphere may be influenced by the lift of neutral atmosphere. According to Xu et al (), the levels where CO 2 density increases during dust storms can extend up to 400 km.…”
Section: Discussionmentioning
confidence: 99%
“…The response of the thermosphere to lower atmospheric dust is generally marked by a rapid increase in the neutral density at a fixed altitude, followed by a slow density decay back to nominal levels over several weeks (England & Lillis, ; Keating et al, ; Lillis et al, ; Withers & Pratt, ; Zurek et al, ). During typical dust events, thermospheric neutral densities increase by a factor of ∼1.5–3.0 at fixed altitudes (Liu et al, ; Withers & Pratt, ; Zou et al, ), but thermospheric neutral temperatures do not drastically change at fixed pressure levels (Fang et al, ; McElroy et al, ; Wang & Nielsen, ). When thermospheric pressure surfaces rise in response to dust loading, the peak of the ionosphere—which typically forms between 120 and 150 km and at a fixed pressure level (Withers, )—rises in altitude.…”
Section: Introductionmentioning
confidence: 99%